Knowledge and Practice on Prevention of Complications of Diabetes Mellitus among Patients with Diabetes in a Tertiary Hospital - Acharya, Om K; KC, Takma; Shrestha, Krishna D (Journal of Institute of Medicine Nepal, 2019)
Introduction: Diabetes is a major contributing factor for overall health status, morbidity, mortality and quality of life. Adequate knowledge and sufficient practice can prevent many possible diabetic complications. Hence, the objective of this study was to find out the knowledge and practice regarding prevention of complications of diabetes among diabetic patients. Methods: A descriptive, cross sectional design was carried out in Tribhuvan University Teaching Hospital Kathmandu (TUTH). A total 124 diabetic patients who came for follow-up in endocrine Out Patient Department were selected through purposive sampling technique by using pre-tested structured interview schedule during four weeks. Data was analyzed by using the descriptive and inferential statistics with the help of Statistical Package of Social Science (SPSS) version 16. Results: The study findings showed that 24.2% respondents had adequate knowledge about complications. More than half of the respondents had sufficient practice (52.4%) regarding prevention of diabetic complications. Association between knowledge and selected variables showed that sex and education level tends to be significantly associated and regarding practice, area of residence and duration of illness were significantly associated (p<0.05). There was a statistically significant (p<0.001) and average positive relationship (r=0.605) was found between knowledge and practice. Conclusion: The study concluded that though only few respondents had adequate knowledge, more than half of the respondents had sufficient practice regarding preventing complications. This finding suggests awareness program regarding prevention of complications of diabetes mellitus should be launched periodically to increase knowledge and sufficient practice on prevention of diabetic complications.